An Analysis of Mendel's Two Hybridist Theories and their Intertheoretical Relationships - Lorenzano, Pablo Julio (2022)
Based on a statistical analysis of his experiments, which was a novelty for the tradition of “horticulturalists” (or “plant breeders”) as well as for the tradition of “hybridists”, and seeking a “generally applicable law governing the formation and development of hybrids” (MENDEL 1865: 3), Mendel states “the law of development/evolution found for Pisum” (MENDEL 1865: 32). When he tries to provide the “foundation and explanation” (MENDEL 1865: 32) of the law of formation and development of hybrids, he does it in terms of the production and behavior of egg cells and pollen cells, and, ultimately, in terms of the nature and behavior of what he calls “elements” (MENDEL 1865: 41) or “cell elements” (MENDEL 1865: 42). Moreover, Mendel recognizes the existence not just of hybrids that behave like those of Pisum – i.e., of “variable hybrids” – but also of hybrids that “remain perfectly like the hybrid and continue constant in their offspring” (MENDEL 1865: 38) and “acquire the status of new species” (MENDEL 1865: 40) – i.e., of “constant hybrids” (MENDEL 1869: 27–28, 31). The law that would govern the behavior of constant hybrids would also find its foundation and explanation in terms of the nature and behavior of elements (or cell elements). Mendel’s hybridism consists of two theories: a theory that moves on a more “empirical” level, according to Schleiden’s first “special guiding maxim”, the “Maxim of the history of development/evolution” (SCHLEIDEN 1849: 141, 142, 146), which can be called “Mendel’s theory of the development/evolution of hybrids” (DEH), and a theory that moves on a more “theoretical” level, according to Schleiden’s second “special guiding maxim”, the “Maxim of the autonomy of cells in plants” (SCHLEIDEN 1849: 146, 148), which can be called “Mendel’s theory of the cellular foundation of the development/evolution of hybrids” (CFH). The paper aims to present an analysis of these two theories and their intertheoretical relationships, carried out within the framework of the so-called Metatheoretical Structuralism (BALZER, MOULINES & SNEED 1987).